Defining pseudoprogression in glioblastoma multiforme. Issue 10 (17th May 2013) - Van, E.; Wozniak, A.; Geussens, Y.; Menten, J.; De, S.; Van, F.; Sciot, R.; Van, S.; Bechter, O. E.; Demaerel, P.; Wilms, G.; Clement, P. M.
<x xml:space="preserve">Abstract</x> Background and purpose Pseudoprogression is a frequent phenomenon observed since the introduction of postoperative therapy with radiotherapy and temozolomide (RT/TMZ) in glioblastoma multiforme (GBM) patients. However, the criteria defining pseudoprogression, its incidence, the time of occurrence and its impact on therapy and outcome remain poorly defined. Methods The objective of this study is to compare two sets of criteria (liberal and stringent), defining pseudoprogression, in a cohort of patients treated before and after the introduction of RT/TMZ in the standard postoperative treatment. This retrospective review includes 136 unselected and consecutively treated patients with pathologically diagnosed GBM. Results Pseudoprogression was observed in 10 (12%) cases applying the stringent criteria, and in 18 (23%) patients when using the liberal criteria, in the cohort treated with RT/TMZ. Pseudoprogression was observed in only one patient treated with RT alone. The median time to pseudoprogression was 4 weeks after the end of RT. Patients with pseudoprogression had a median survival time of 28 months, compared with 12 months for patients without pseudoprogression. Conclusions The incidence of pseudoprogression after RT/TMZ strongly depends on the applied criteria. However, regardless of the stringency of the criteria, the impact on survival remains the same.